Levels of Some Endogenous Plant Hormones During the Flowering Period in Loquat (Eriobotrya japonica Lindl.) - ERSOY, NILDA; KAYNAK, LAMI; KANKAYA, ABDULLAH (Asian Journal of Chemistry, 2010)
Changes in the amount of endogenous phytohormones were determined in loquat flowers. Samples were chosen among flowers in the beginning bloom stage, full bloom stage and the end of the flowering period. Among these samples, amounts of free-, bound- and total-forms of some endogenous plant hormones (indole-3-acetic acid, gibberellic acid, abscisic acid, zeatin) were separated from plant extract and quantified by high performance liquid chromatography using a reversedphase C18 column. According to the results, indole-3-acetic acid level did not change during the flowering period in Gold Nugget cultivar, but it was observed to be high in Akko XIII cultivar in the initiation of flowering period. Level of gibberellic acid in the flowers decreased from initiation of flowering period till the end of it. During flowering period abscisic acid level dramatically increased and reached its maximum, which indicates that abscisic acid might play an active role in flowering process. Zeatin was observed in high levels in both the initiation and the end of flowering period. Its level, however, was determined to be minimum at the full bloom stage.